1988
DOI: 10.1139/f88-251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Induction of Liver Tumours in Rainbow Trout (Salmo gairdneri) by Contaminated Sediment from Hamilton Harbour, Ontario

Abstract: Sediments from Hamilton Harbour and an uncontaminated control site were collected and extracted for organic contaminants to investigate the putative association between chemical contaminants and high incidences of fish tumours in Hamilton Harbour. Sediment extract from Hamilton Harbour had high levels of polynuclear aromatic hydrocarbons and was mutagenic in the Ames bacterial mutagenicity assay. In two sets of experiments using a trout sac-fry microinjection route of exposure, Hamilton Harbour sediment extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 2 publications
1
27
0
1
Order By: Relevance
“…Although experimental evidence has shown that liver neoplasms can be induced by exposure of fish to contaminated sediments (Metcalf et al 1988;, the development of these lesions is thought to occur slowly. Furthermore, it has been suggested that regression and re-modelling of lesions such as hepatocellular FCA, back into normal parenchyma is possible if the stimulating contaminant is removed (Myers et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental evidence has shown that liver neoplasms can be induced by exposure of fish to contaminated sediments (Metcalf et al 1988;, the development of these lesions is thought to occur slowly. Furthermore, it has been suggested that regression and re-modelling of lesions such as hepatocellular FCA, back into normal parenchyma is possible if the stimulating contaminant is removed (Myers et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus, however, that vacuolated hepatocytes are frequently found proximal to neoplasms and that tumor prevalence is associated with increasing numbers of vacuolated liver cells and that, the extent of deformity and cell injury is also consistent with hepatotoxicant action [4,11]. PAH's have been implicated in the development of liver carcinogenesis [5,14,30] and a cause and effect relationship between PAH's and liver tumors or preneoplastic lesions in fish has been established by in-vitro studies [16,28]. Our observations in the present study could be attributable in part to this chemical group, as measurable levels of heavy metals, hydrocarbons, organo-chlorines, PAH's and PCB's have been reported in the Lagos lagoon complex by Ajao et al [1].…”
Section: Discussionmentioning
confidence: 99%
“…The discussion below interprets the toxicological significance, to the extent possible, of the complex associations between lesion types and measures of potential contaminant exposure, actual dietary uptake, hepatic Volume 102, Number 2, February 1994 aAnalyses were performed separately while adjusting for mean age and gender ratio (female:male). (2,10-12, 75,76) and which significantly co-occur with neoplasms in English sole (18) (3,15,24,25,39,59), in studies in other species of wild fish (69,77,78) and the hepatocarcinogenicity of genotoxic PAHs in laboratory studies with fish (5,41,42,(79)(80)(81). XPAHs in sediment from English sole sites ranged from undetectable at the Nisqually River reference site to 5900 ng/g in Elliott Bay, comparable to levels in previous studies where the relationship between PAH exposure and neoplasms was first established in this species (15).…”
Section: Relationships Between Chemical Contaminants and Hepatic Lesionsmentioning
confidence: 99%